2012
DOI: 10.1111/j.1476-5381.2011.01775.x
|View full text |Cite
|
Sign up to set email alerts
|

Field and action potential recordings in heart slices: correlation with established in vitro and in vivo models

Abstract: BACKGROUND AND PURPOSE Action potential (AP) recordings in ex vivo heart preparations constitute an important component of the preclinical cardiac safety assessment according to the ICH S7B guideline. Most AP measurement models are sensitive, predictive and informative but suffer from a low throughput. Here, effects of selected anti‐arrhythmics (flecainide, quinidine, atenolol, sotalol, dofetilide, nifedipine, verapamil) on field/action potentials (FP/AP) of guinea pig and rabbit ventricular slices are present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 95 publications
4
24
0
Order By: Relevance
“…hERG) (Himmel et al, 2012). These findings are in agreement with other studies in conscious telemetred dogs in which similar doses of atenolol were administered (Himmel et al, 2012;Norton, Iacono, & Vezina, 2009).…”
Section: Cardiovascular Data From the Conscious Dog Telemetry Modelsupporting
confidence: 92%
See 1 more Smart Citation
“…hERG) (Himmel et al, 2012). These findings are in agreement with other studies in conscious telemetred dogs in which similar doses of atenolol were administered (Himmel et al, 2012;Norton, Iacono, & Vezina, 2009).…”
Section: Cardiovascular Data From the Conscious Dog Telemetry Modelsupporting
confidence: 92%
“…A statistically significant difference in QTcR occurred at the 60 min time point after verapamil at both sites but this was inconsistent and, in both cases, this was an isolated occurrence. Other studies in conscious dogs have shown that similar doses of verapamil, a multi-cardiac ion channel blocker, had no effect on QTc interval (Himmel et al, 2012;Toyoshima et al, 2005).…”
Section: Cardiovascular Data From the Conscious Dog Telemetry Modelmentioning
confidence: 98%
“…Flecainide is used widely as a class Ic antiarrhythmic drug that, in addition to inhibiting cardiac sodium channels, displays class III antiarrhythmic activity due to inhibition of Kv4.3 and hERG [31,32]. In an elegant study, Caballero and colleagues reported [33] that clinical doses of flecainide increase ventricular I K1 through potentiation of Kir2.1, but not of Kir2.2, Kir2.3, Kir2.1/2.2 or Kir2.1/2.3 channels.…”
Section: Cardiac Kir2x Channelsmentioning
confidence: 99%
“…; Himmel et al . ), thus providing a promising experimental model for electrophysiology, Ca 2+ handling, and drug action investigations.…”
Section: Introductionmentioning
confidence: 99%